Help! I'm stuck in a giant nostril! - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2011)
George's fourth-grade field trip to the science museum is ruined by one magic burp after another, causing him to wreak havoc on the exhibits and lose a bet to a classmate.
550
Accelerated Reader AR
Keywords: Belching -- Juvenile fiction; School field trips -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Juvenile fiction